2019
DOI: 10.1021/acs.jafc.8b06674
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Plant Polyphenols to Serum Albumin and LDL: Healthy Implications for Heart Disease

Abstract: Cardiovascular disease (CVD) is the leading cause of death in industrialized nations. The initiating event in atherosclerosis, or hardening of the arteries, is oxidation of low density lipoprotein (LDL). Binding with serum albumin and LDL of 41 polyphenols (major antioxidants in plant foods) constituting four classes of flavonoids, three types of phenolic acids, and seven polyphenol conjugate metabolites was investigated indirectly by fluorescence quenching and directly by affinity separation/high-performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Poloni et al [174] carried out a systematic investigation comparing the binding of 41 plant polyphenols, which bear potent antioxidant properties, to serum albumin and LDL isolated from pigs. By monitoring quenching of intrinsic fluorescence of albumin and apoB-100 on LDL following addition of polyphenols, they reported that the calculated quenching constant and binding were in general higher for albumin compared to LDL.…”
Section: Antioxidant Anti-inflammatory and Anti-atherogenic Agentsmentioning
confidence: 99%
“…Poloni et al [174] carried out a systematic investigation comparing the binding of 41 plant polyphenols, which bear potent antioxidant properties, to serum albumin and LDL isolated from pigs. By monitoring quenching of intrinsic fluorescence of albumin and apoB-100 on LDL following addition of polyphenols, they reported that the calculated quenching constant and binding were in general higher for albumin compared to LDL.…”
Section: Antioxidant Anti-inflammatory and Anti-atherogenic Agentsmentioning
confidence: 99%
“…The total antioxidant capacity of barley and oat grain was subject to the effect of both environmental factors (weather conditions, fertilization, etc.) and the genotype (Polonskiy et al, 2016а;Mareček et al, 2017). To assess the effect of the genotype, year and place of growing on the content of protein, lipids, tocol and lutein in whole-grain flour, samples of einkorn wheat and samples of common wheat were cultivated for two years in four different places in Italy.…”
Section: Plant Sciencementioning
confidence: 99%
“…Apart from that, the binding of plant polyphenols has been associated with cardiovascular benefits in relation to LDL oxidation. Various plant phenols such as quercetin, resveratrol, PCA and PHBA have showed their ability to relatively bind with LDL [39]. It has been reported that the binding of LDL by plant phenols showed better resistance to oxidation than LDL alone [40].…”
Section: Of 18mentioning
confidence: 99%